Antibiotic Sensitivity in Post Cesarean Surgical Site Infection at a Tertiary Care Centre in Eastern Nepal - Chhetry, Manisha; Subedi, Shanti; Ghimire, Sita; Lamichanne, Sabina; Banerjee, Basudeb; Singh, Ganesh Kumar (Journal of Lumbini Medical College, 2017)
Introduction: Post cesarean surgical site infection (SSI) is one of the common complications diagnosed in 2.5%-16% of the cases and is associated with significant increase in maternal morbidity, hospital stay, costs, and psychological stress to the new parents. This study was designed to study the incidence of SSI and the antimicrobial resistance pattern in our hospital. Methods: This was a prospective observational study conducted from July 2015 to December 2015, in which all patients who were admitted with post cesarean SSI or developed SSI during their stay were included. Wound specimens were collected and susceptibility testing was carried out using disc diffusion technique. Results: The incidence of post cesarean SSI was 6.07% (47/774). Out of the 47 patients who had SSI, 35 (74.75%) had positive swab culture. The most important organism isolated was Staphylococcus aureus (82.85%) out of which 17 (58.62%) were MRSA strain. Resistance of Staphylococcus to penicillin was 84.6% whereas amikacin was found to be highly sensitive (>96%). Among the MRSA strain, resistance to ciprofloxacin, which is the currently used drug for prophylaxis, was 94%. Resistance to penicillins, cephalosporins, and clavulanate was also high. Resistance to vancomycin was also high (53%). Amikacin and chloramphenicol were found to be highly sensitive (94% and 90% respectively) in the MRSA group. Conclusion: MRSA is the leading cause of post cesarean SSI and is a matter of great concern. Amikacin and chloramphenicol were found to be highly sensitive in this group but unlike other studies, resistance of vancomycin was showing an increasing trend. J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, page: 55-59 DOI: https://doi.org/10.22502/jlmc.v4i2.90